The Relationship Between Hedonistic Lifestyle and Financial Literacy with Student Consumption Behavior in Buying Drinks at Coffee Shops: Hubungan Antara Gaya Hidup Hedonis dan Literasi Keuangan dengan Perilaku Konsumtif Mahasiswa dalam Membeli Minuman di Kedai Kopi - Chandrika Kumarasetya Anamel; Wisynu Ari Gutama; Andrean Eka Hardana (Jurnal Ilmiah Manajemen Agribisnis, 2026)
Globalization that is growing rapidly throughout the world causes changes in student consumptive behavior, especially in buying drinks at coffee shops. The emergence of a person's consumptive behavior is usually also associated with a hedonistic lifestyle and financial literacy. This study aims to analyze the relationship between hedonic lifestyle and financial literacy with consumptive behavior of students in buying drinks at coffee shops. Determination of the sample in this study using a non-probability sampling approach with purposive sampling method with a total sample of 322 respondents. The hypothesis testing method used is multiple linear regression and Pearson product moment correlation with the help of the IBM SPSS 26 program. The results show that the hedonic lifestyle has a positive direction and a very strong relationship with consumptive behavior, while financial literacy has a negative direction and weak relationship with consumptive behavior.